Ambivalent Speciesism - Albersmeier, Frauke (Les ateliers de l'éthique / The Ethics Forum, 2024)
This paper explores the idea of ambivalent speciesism—speciesism that expresses itself both in hostile and benevolent attitudes and behaviours, while remaining, overall, disrespectful or inconsiderate towards members of certain species. It has long been acknowledged that phenomena such as racism and sexism are marked by ambivalence. The same is likely to be the case with respect to speciesism. This prospect has conceptual implications because making sense of positively valenced components of speciesism requires clarifying the connection between discrimination and prejudice. After raising this conceptual issue, this paper focuses on outlining possible patterns of ambivalent speciesism, distinguishing ambivalence from complex negativity and indicating benevolent speciesism’s potential to harm animals. Benevolent speciesism can come with some local benefits for some animals but eventually harms them by working as a facilitating factor for their subordination, underpinning negligence and entailing punishment when positive stereotypes are disappointed. While hostile speciesism rightly draws our attention, we should also look out for its positive forms which are likely to become more practically relevant as efforts for the recognition of animals’ moral considerability are underway.